2007
DOI: 10.1016/j.im.2006.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Public grid computing participation: An exploratory study of determinants

Abstract: Using the Internet, "public" computing grids can be assembled using "volunteered" PCs. To achieve this, volunteers download and install a software application capable of sensing periods of low local processor activity. During such times, this program on the local PC downloads and processes a subset of the project's data. At the completion of processing, the results are uploaded to the project and the cycle repeats.Public grids are being used for a wide range of endeavors, from searching for signals suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…Several studies have noted that personal innovativeness is a significant predictor for perceived ease of use (Lu et al, 2005;Serenko, 2008;Yi et al, 2006) and behavioral intentions (Crespo and Rodriguez, 2008;Taylor, 2007). Hence, the next section discusses personal innovativeness.…”
Section: Tammentioning
confidence: 94%
“…Several studies have noted that personal innovativeness is a significant predictor for perceived ease of use (Lu et al, 2005;Serenko, 2008;Yi et al, 2006) and behavioral intentions (Crespo and Rodriguez, 2008;Taylor, 2007). Hence, the next section discusses personal innovativeness.…”
Section: Tammentioning
confidence: 94%
“…Agarwal and Prasad [ 56 ] empirically tested the influence of personal innovativeness in IT on information technology use. Many existing studies have demonstrated that personal innovativeness in IT significantly influences the intention to use a new technology such as internet [ 57 ], public grid computing [ 58 ], PDA [ 59 ], information systems [ 60 ] and mHealth [ 54 ]. Consequently, the following hypothesis is suggested: : Personal innovativeness in IT has a positive influence on the intention to use mHealth services among younger in Bangladesh.…”
Section: Personal Innovativeness In Itmentioning
confidence: 99%
“…For example Hsu and Lin (2008) proposed that customer beliefs about technology acceptance and knowledge sharing had an impact on their attitudes toward using blogs. In addition Taylor (2007) argued that customers' motives for volunteering had an impact on their attitudes toward participation in public grid computing initiatives. Lu and Lin (2003) indicated that customer beliefs about a particular website's content, context, and infrastructure would influence their attitudes towards using the site for repeated transactions.…”
Section: Tra and Related Studiesmentioning
confidence: 99%